Hermeneutika Friedrich August Wolf Membongkar Lapisan Makna Teks Kuno : Hermeneutika, Friedrich August Wolf, Teks Kuno, Filologi Klasik (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This paper tries to discuss Friedrich August Wolf's hermeneutics in the grammatical interpretation of ancient texts historically and philosophically. The purpose of this paper is to explain Friedrich August Wolf's concept of hermeneutics in understanding ancient texts. Wolf, a classical philologist, contributed greatly to developing methods of interpreting texts that allowed readers to unearth the layers of hidden meanings behind ancient literary works. Wolf introduced an interpretive method that was not only limited to literal reading, but also included a deeper understanding of the historical, social, and cultural context behind the text. Wolf's hermeneutics not only focuses on literal understanding, but also considers the historical, social, and cultural contexts that surround the text. Wolf's hermeneutics emphasizes the importance of critical analysis and language structure, which not only enriches the understanding of the text itself, but also offers a new way of interpreting classical works. With this approach, Wolf introduced a comprehensive interpretive framework, which allows for more in-depth and structured analysis of the text. This study aims to describe how Wolf's hermeneutic method became an important foundation in the study of philology and interpretation of classical texts, as well as its relevance to contemporary approaches in understanding ancient literary works.
Keywords: Hermeneutics; Friedrich August Wolf; Ancient Texts; Classical Philology